A Chemokine CXCL14 and Its Relationship to Biomarkers for Both Small and Non-Small Cell Carcinomas - Noman, Wisam Abdulameer; Addai Ali, Hanaa (Journal of Neonatal Surgery, 2025)
Worldwide, lung cancer is still the biggest killer when it comes to cancer, arising from uncontrolled cell division in lung tissues. A homeostatic chemokine with a high degree of conservation, CXCL14 is expressed in epidermal epithelia, playing a key role in immune cell maturation and epithelial regulation. It is the only chemokine known to localize within the tumor microenvironment, contributing to immune surveillance. This study aims to evaluate CXCL14 as a possible of biomarker a prediction of lung cancer outcomes. The materials and methods are a case-control study conducted on 180 participants (aged 45–77): There were 36 cases of “SCLC is a kind of LC”, 54 cases of “LC of (NSCLC)”, and 90 were healthy controls. CXCL14 levels were measured using ELISA, along with CBC, cholesterol, triglycerides, and liver enzymes (ALT, AST, ALP). Statistical analysis assessed correlations between CXCL14 and (LC) progression. The findings for a study demonstrated that CXCL-14 levels are seen to a significantly lower in stage III compared to stage IV in both NSCLC and SCLC, with a more pronounced decline in NSCLC at stage IV. Linear regression showed a positive correlation between CXCL14 and cholesterol, triglycerides, NLR, ALT, AST, and ALP, while a negative correlation was observed with hemoglobin (Hb) and HDL. CXCL14 demonstrated high diagnostic accuracy, with cut-off values of 120.007 pg/mL for SCLC (AUC = 0.846, p = 0.000) and 87.054 pg/mL for NSCLC (AUC is 0.832, p is 0.000). Conclusions, these findings offer that CXCL14 is a promising biomarker for lung cancer diagnosis and monitoring. Its involvement in lung cancer cell motility also highlights its potential role in predicting metastasis, making it a valuable tool for early detection and prognosis.